2019
DOI: 10.1016/j.mex.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Method for quantitative and qualitative evaluation of hazardous waste in laboratories of Isfahan University of Medical Sciences, Iran

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Anode: 2 H2O (aq) → O2 (g) + 4 H + (aq) + 4e -(1) Cathode: 2 H2O (aq) + 2e-→ H2 (g) + 2 OH -(aq) (2) The high amount of bubble distribution was obtained at size categories of <0.5; 0.5; >0.5 mm respectively for 80, 18, and 13 at the cathode while at the anode was 70, 18, and 9 when electroflotation was operated in the constant voltage of 21 V. The bubble sizes were important in the electroflotation of fine particles since these parameters were covering the collision, adhesion, and transport mechanism the flotation process [13]. The recovery process of the electro-flotation for the dispersed phase could be regulated by various parameters such as pH solution and the presence of special additives (coagulants) [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anode: 2 H2O (aq) → O2 (g) + 4 H + (aq) + 4e -(1) Cathode: 2 H2O (aq) + 2e-→ H2 (g) + 2 OH -(aq) (2) The high amount of bubble distribution was obtained at size categories of <0.5; 0.5; >0.5 mm respectively for 80, 18, and 13 at the cathode while at the anode was 70, 18, and 9 when electroflotation was operated in the constant voltage of 21 V. The bubble sizes were important in the electroflotation of fine particles since these parameters were covering the collision, adhesion, and transport mechanism the flotation process [13]. The recovery process of the electro-flotation for the dispersed phase could be regulated by various parameters such as pH solution and the presence of special additives (coagulants) [14].…”
Section: Resultsmentioning
confidence: 99%
“…Activities in the chemical laboratory need more chemicals either as main or supporting material, such as acid and alkaline for organic and inorganic synthesis [1]. The chemicals used at the laboratory would be the disposal of and produced a characteristic of toxicity and hazardous [2]. Toxicity and hazardous materials cause directly or indirectly environmental pollution which covering health and ecological organism [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods of treatment may be used before disposing HW such as incineration, neutralization, and chemical fixation. A good planning is also necessary to meet the recommended requirements of storing, disposing, and treating HW in order to avoid their potential impact on the environment and public health (Pourzamani et al, 2019) Unfortunately, there are no reported data and existing regulations related to HWM knowledge and practices of academic laboratories in public university in Lebanon. Consequently, the objective of this study was to assess for the first time the HWM knowledge of workers in scientific university laboratories in the public university in Lebanon of and to explore the factors associated with such knowledge on HWM.…”
Section: Introductionmentioning
confidence: 99%